ผลสัมฤทธิ์ทางการเรียนของนักเรียนชั้นประถมศึกษาปีที่ 6 ในการศึกษานอกสถานที่แบบการใช้ความเป็นจริงเสมือนกับแบบการใช้ความเป็นจริงเสมือนและการเรียนเป็นคู่ - วิรงรอง วงษ์วัฒนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research was to compare the academic achievement of the sixth grade students in virtual field trip using virtual reality with learning cell. The samples were 60 sixth grade students from Chulalongkorn University Demonstration Elementary School by purposive selection. This research separated the samples into two treatment groups which contained 30 students in each group. The first group studied the virtual field trip using virtual reality and the second group studied the virtual field trip using virtual reality with learning cell. The research instruments were the educational virtual field trip using virtual reality "Living Things on the Reefs", the learning achievement test and the questionnaires about using educational virtual field trip using virtual reality for the samples. The data were analyzed by means, standard deviation and One-way ANOVA. The research results were as follows: 1. The post-test score of both groups of students were higher than pre-test score at the .05 significant level. 2. The post-test score of students who studied in field trip using virtual reality with learning cell was statistically significant higher than students who studied in field trip using virtual reality at the .05 significant level.